2016
DOI: 10.4103/2249-4863.197311
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rubella-specific IgG antibodies in unimmunized young female population

Abstract: Context:Rubella is a mild self-limiting disease all over the world; nevertheless, it is of significant public health importance due to its teratogenic effect of congenital rubella syndrome. Rubella vaccine is currently not included in the national immunization program in India. Rubella-specific IgG in the unvaccinated population is a marker of previous rubella infection. Rubella IgG estimation in children will provide data for initiation and necessary modification to the immunization strategy.Aims:In this back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The prevalence of Rubella-specific IgG antibodies was found to be 68.3% among non-vaccinated girls in the age group of 13-15 years as noted by a study from Kerala, South India. The same study had observed that the seropositive girls had unprotective Rubella-specific IgG antibody titers [7]. This makes them potential carriers of infection to the fetuses during pregnancy and the development of congenital Rubella syndrome (CRS).…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of Rubella-specific IgG antibodies was found to be 68.3% among non-vaccinated girls in the age group of 13-15 years as noted by a study from Kerala, South India. The same study had observed that the seropositive girls had unprotective Rubella-specific IgG antibody titers [7]. This makes them potential carriers of infection to the fetuses during pregnancy and the development of congenital Rubella syndrome (CRS).…”
Section: Discussionmentioning
confidence: 93%
“…The ramifications of Rubella infections can be kept under check when the "herd immunity threshold" is maintained above 83% among adults in the country without any regional imbalances. The first dose of MMR vaccine should be started as early as 15-18 months of the age and second dose at 6-12 years in order to eradicate the CRS in India (Jayakrishnan Thayyil et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Mirambo M et al, in a systematic review, report that the seroprevalence of IgG rubella antibodies in Africa is high but with a substantial number of women of childbearing age being susceptible to rubella infection. Some seroepidemiological surveys from countries in Asia have reported that a substantial number of women reach childbearing age without acquiring natural immunity to rubella, making them more susceptible to infection [17][18] . In Europe, routine immunization has changed the epidemiology of rubella -increased seroprevalence of IgG antibodies and decreased morbidity.…”
Section: Discussionmentioning
confidence: 99%